Interleukin-6 May Contribute to Mortality in Parkinson’s Disease Patients: A 4-Year Prospective Study - Michal Dufek; Irena Rektorova; Vojtech Thon; Jindrich Lokaj; Ivan Rektor (Parkinson's Disease)
Objectives. The association between abnormal serum immunomarkers and mortality in 53 consecutive Parkinson’s disease patients was studied. Materials and Methods. The plasma level of specific inflammatory cytokines was investigated: mannan-binding lectin (MBL), interleukin- (IL-) 6, and tumor necrosis factor-alpha (TNF-α). The baseline serum immunomarkers obtained from patients who died (n=16) during a four-year follow-up period were compared with the data of patients who survived (n=37). Results. The baseline level of IL-6 was significantly higher in the deceased patients than in the survivors. Elevated IL-6 levels and age were major independent contributors to disease mortality. Differences between other plasma cytokine level abnormalities were not significant. Conclusion. This study showed that IL-6 elevation may be a marker of increased mortality risk in Parkinson’s disease patients. The inflammation may act in association with other factors and comorbidities in progressive neurodegenerative pathology.